2018
DOI: 10.1177/0894845318803192
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perfectionism on Career Adaptability and Career Decision-Making Difficulties

Abstract: This study investigated categorization of perfectionism subtypes for Chinese undergraduates and the effects of perfectionism subtypes on career outcomes based on two prominent, competing models of perfectionism, the tripartite model and 2 × 2 model. Indices of career outcome were defined with career adaptability (positive) and career decision-making difficulties (negative). The results of both cluster analysis and latent profile analysis coincided with the four-subtype structure of the 2 × 2 model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
(74 reference statements)
0
4
1
Order By: Relevance
“…The total scores of career adaptability for university new graduates in this study were pretty higher than those of sophomores and juniors (97.16 ± 11.12 vs 88.56 ± 12.24, t = 25.92, p < 0.01) investigated by Wang et al (2020), and higher than those of frontline hotel employees (93.54 ± 20.82, t = 10.92, p < 0.01) reported by Karatepe and Olugbade (2017). During our investigation, the employment of new graduates has just begun.…”
Section: Discussioncontrasting
confidence: 48%
“…The total scores of career adaptability for university new graduates in this study were pretty higher than those of sophomores and juniors (97.16 ± 11.12 vs 88.56 ± 12.24, t = 25.92, p < 0.01) investigated by Wang et al (2020), and higher than those of frontline hotel employees (93.54 ± 20.82, t = 10.92, p < 0.01) reported by Karatepe and Olugbade (2017). During our investigation, the employment of new graduates has just begun.…”
Section: Discussioncontrasting
confidence: 48%
“…Therefore, this study proposes that personality traits are core factors in the career decision-making process. The mixed perfectionism sub-types as entailing a high risk with regard to career decision-making, while non-perfectionism sub-types were associated with low career decision-making difficulties ( Wang et al, 2020 ). College students pursued “perfection” to a greater or lesser degree and exhibited a higher level of career decision-making difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, perfectionism can positively or negatively influence CA, in addition to one's basic orientation toward life. Wang et al (2018) reported that perfectionism significantly affects one's CA. One's motivation for perfection affects efforts to achieve performance, accomplish standards, and assess their own or others' behavior and performance (Flett & Hewitt, 2002;Frost et al, 1990).…”
Section: Adlerian Theory On Camentioning
confidence: 99%